2019
DOI: 10.1002/gj.3578
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoproductivity and organic matter accumulation during the deposition of the Chang 7 organic‐rich shale of the Upper Triassic Yanchang Formation, Ordos Basin, China

Abstract: The lacustrine Chang 7 organic‐rich shale of the Upper Triassic Yanchang Formation is a very important hydrocarbon source rock and contains high total organic carbon content (average = 5.54 wt.%). Previous studies suggest that deposits of the Chang 7 accumulated slowly under dominantly oxic–suboxic bottom‐water conditions occasionally interrupted by the establishment of anoxic conditions. However, questions remain regarding the role of palaeoproductivity in accumulation of the Chang 7 organic matter. Palaeopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The former is closely related to primary productivity, while the latter is mainly related to redox conditions and sedimentation rate (Demaison and Moore, 1980;Pedersen and Calvert, 1990;Calvert and Pedersen, 1993;Curiale and Gibling, 1994;Jones and Manning, 1994;Hay, 1995;Parrish, 1995;Algeo et al, 2011;Ding et al, 2015;Wang et al, 2017;Yuan et al, 2020). Previous studies have found that the sedimentation rate of the Chang 7 Member in the Ordos Basin has little effect on the enrichment of organic matter (Yuan et al, 2016(Yuan et al, , 2020. Therefore, the enrichment of organic matter in the Chang 7 shale is mainly related to paleoproductivity and redox conditions.…”
Section: Relationship Between Hydrothermal Activity and Organic Matte...mentioning
confidence: 98%
See 2 more Smart Citations
“…The former is closely related to primary productivity, while the latter is mainly related to redox conditions and sedimentation rate (Demaison and Moore, 1980;Pedersen and Calvert, 1990;Calvert and Pedersen, 1993;Curiale and Gibling, 1994;Jones and Manning, 1994;Hay, 1995;Parrish, 1995;Algeo et al, 2011;Ding et al, 2015;Wang et al, 2017;Yuan et al, 2020). Previous studies have found that the sedimentation rate of the Chang 7 Member in the Ordos Basin has little effect on the enrichment of organic matter (Yuan et al, 2016(Yuan et al, , 2020. Therefore, the enrichment of organic matter in the Chang 7 shale is mainly related to paleoproductivity and redox conditions.…”
Section: Relationship Between Hydrothermal Activity and Organic Matte...mentioning
confidence: 98%
“…The enrichment of organic matter is mainly controlled by the supply and preservation of organic matter (Arthur and Sageman, 1994;Sun, 2013;Ding, 2014;Wang et al, 2017). The former is closely related to primary productivity, while the latter is mainly related to redox conditions and sedimentation rate (Demaison and Moore, 1980;Pedersen and Calvert, 1990;Calvert and Pedersen, 1993;Curiale and Gibling, 1994;Jones and Manning, 1994;Hay, 1995;Parrish, 1995;Algeo et al, 2011;Ding et al, 2015;Wang et al, 2017;Yuan et al, 2020). Previous studies have found that the sedimentation rate of the Chang 7 Member in the Ordos Basin has little effect on the enrichment of organic matter (Yuan et al, 2016(Yuan et al, , 2020.…”
Section: Relationship Between Hydrothermal Activity and Organic Matte...mentioning
confidence: 99%
See 1 more Smart Citation
“…The organic‐rich shales in the Yanchang Formation have been considered to be the main hydrocarbon source rock and provide the main reservoir of oil for the Mesozoic petroleum system (Qiu et al, 2014; Yang & Zhang, 2005; Zou et al, 2019). A high primary productivity level and oxic–suboxic bottom water conditions, occasionally interrupted by anoxic conditions, are considered to be the main factors that control the formation of the hydrocarbon resource potential of organic‐rich shales in the Yanchang Formation (Qiu, 2011; Qiu et al, 2015; Yang et al, 2010; Yang & Deng, 2013; Yang & Zhang, 2005; Yuan et al, 2017; Yuan, Liu, Zhou, Xu, & Li, 2019). Similarly, thick organic‐rich shales are also developed in the Middle Triassic Tongchuan Formation, which immediately underlies the Upper Triassic Yanchang Formation.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest known appearance of a Mesozoic‐type of tropical, multi‐levelled lacustrine ecosystem after the end‐Permian mass extinction is reported from these shales (Zhao et al, 2020). Up till now, studies of the depositional environment of the Tongchuan shales have been lacking, although it is of significance for understanding the formation and preservation of organic‐rich shales and lacustrine fossils (Yuan et al, 2019; Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%